2010
DOI: 10.1007/s10706-010-9348-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil Permeability Controlled by Particle–Fluid Interaction

Abstract: In this paper, Atterberg limits and hydraulic conductivity tests are performed in sand samples mixed with different amounts of silt, zeolite and bentonite. The testing liquids consist of kerosene, two paraffin oils with different viscosities, distilled water and 1, 10 and 1,000 mol/m 3 calcium chloride solutions. Experimental results show that soils completely lost their plasticity when are in contact with light nonaqueous phase liquids, and that the liquid limit depends on the dynamic viscosity of the fluid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
(31 reference statements)
2
9
0
3
Order By: Relevance
“…The greater the particle's specific surface, the greater the change in liquid limit and electrical sensitivity. These trends are in good agreement with the emergent hydraulic conductivities reported by Montoro and Francisca (2010), who analyzed the influence of particle-fluid interaction on hydraulic conductivity by testing soils with deionized water, nonpolar organic fluids, and ionic solutions. They determined that the Kozeny-Carman equation represents reasonably well measured hydraulic conductivities for the same soil shown in Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The greater the particle's specific surface, the greater the change in liquid limit and electrical sensitivity. These trends are in good agreement with the emergent hydraulic conductivities reported by Montoro and Francisca (2010), who analyzed the influence of particle-fluid interaction on hydraulic conductivity by testing soils with deionized water, nonpolar organic fluids, and ionic solutions. They determined that the Kozeny-Carman equation represents reasonably well measured hydraulic conductivities for the same soil shown in Fig.…”
supporting
confidence: 90%
“…The discussers highlight the relevance of fluid chemistry in reactive porous media behavior (e.g., fine-particle soils with high swelling minerals contents). Particle-fluid interactions that take place at a microscale are very often responsible for the macroscopic behavior of soils [e.g., changes in hydraulic conductivity reported by Montoro and Francisca (2010), soil compressibility reported by Tiwari and Ajmera (2014), and liquid sorption capacity reported by Benson et al (2014)]. Results reported by these authors clearly show that observed behavior of fine soils with similar particle size distribution and similar plasticity but different mineralogy and affinity with water molecules can be attributed to a very different electrical susceptibility, still not captured by current soil classification systems.…”
mentioning
confidence: 99%
“…Es decir, si un líquido altera la permeabilidad intrínseca de un suelo, significa que la red de poros del mismo se vio afectada (Fernandez y Quigley 1988). En las arcillas esmectíticas esta alteración está causada por el mayor o menor hinchamiento provocado por la hidratación (Montoro y Francisca 2010). Los valores de conductividad hidráulica y permeabilidad intrínseca de las mezclas arcilla-arena ensayadas se muestran en el cuadro IV.…”
Section: Resultados Y Discusiónunclassified
“…En el caso del lixiviado, la conductividad hidráulica disminuyó en los primeros meses, pero luego aumentó gradualmente hasta alcanzar un valor final de aproximadamente un orden de magnitud mayor respecto al agua. Este incremento está vinculado a cambios en la interfase fluido-partícula, provocados por la composición del lixiviado, que conduciría a una modificación del equilibrio químico como resultado del intercambio de cationes entre la solución y la arcilla (Benson et al 2010, Montoro y Francisca 2010. Un nuevo equilibrio químico entre la bentonita CATAE y la fangolita NTOL, con el fluido que ocupa los poros, se alcanzó luego de varios meses debido a que la presencia de múltiples iones en el lixiviado conduce a una mayor competencia entre ellos por los sitios activos de la arcilla.…”
Section: Resultados Y Discusiónunclassified
“…Capillary forces and changes in electrical interactions will inherently arise as CO 2 invades the caprock because of the CO 2 -water interfacial tension, water acidification, and the nonpolarity of CO 2 . Eventually, capillary and electrical phenomena upscale, causing mechanical couplings which will affect porosity, clay fabric, hydraulic conductivity, compressibility, and shear strength (similarly to NAPL and clays: Jo et al, 2001;Kaya and Fang, 2005;Montoro and Francisca, 2010;Santamarina et al, 2001b). Yet, the interaction between clay minerals and CO 2 is poorly understood.…”
Section: Introductionmentioning
confidence: 99%